2021
DOI: 10.1186/s13018-021-02727-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative hemoglobin and postoperative moderate and severe anemia among patients undergoing primary total knee arthroplasty: a single-center retrospective study

Abstract: Background Postoperative moderate and severe anemia (PMSA) has been a serious perioperative complication in primary total knee arthroplasty (TKA). However, the ideal cutoff values to predict PMSA is still undetermined. The aim of this study was (1) to identify the risk factors associated with PMSA and (2) to establish the cutoff values of preoperative hemoglobin (HB) associated with increased PMSA in primary TKA. Methods We identified 474 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Several factors were identified to be irrelevant for postoperative anemia, such as age, smoking, drinking, drug taking, high CRP levels, comorbidities, etc. In previous researches, predictors like age, comorbidities, etc showed significant results and were included in the predictive models in previous researches ( 10 , 11 , 32 ); unfortunately, such relevance was not identified in this study, along with other factors such as high CRP levels, smoking, drug taking. The varied results across studies could be explained by diverse composition of patients, different tyoes of surgeries as well as the varied design of the studies.…”
Section: Discussionmentioning
confidence: 70%
“…Several factors were identified to be irrelevant for postoperative anemia, such as age, smoking, drinking, drug taking, high CRP levels, comorbidities, etc. In previous researches, predictors like age, comorbidities, etc showed significant results and were included in the predictive models in previous researches ( 10 , 11 , 32 ); unfortunately, such relevance was not identified in this study, along with other factors such as high CRP levels, smoking, drug taking. The varied results across studies could be explained by diverse composition of patients, different tyoes of surgeries as well as the varied design of the studies.…”
Section: Discussionmentioning
confidence: 70%
“…The prevalence of iron deficiency anemia in non-hospitalized older adults is 16.6–25%; therefore, many patients who are scheduled for TKA may have preoperative iron deficiency anemia [ 23 ]. Preoperative anemia is a major risk factor for 30-day complications, including infection, cardiac complications, and prolonged hospital stay [ 20 , 21 , 30 ]. A preoperative Hb level of < 12.5 g/dL was associated with postoperative transfusion after TKA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative anemia is a known risk factor for delayed postoperative rehabilitation and increased complications [ 20 , 21 ]. A previous study reported that approximately 26% of patients who had undergone elective orthopedic surgery had preoperative anemia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was consistent with other previous comparative studies. Cao, et al found that lower pre-operative hemoglobin (12.1 g/dl) and more intra-operative blood loss (130.9 ml) were independent risk factors for post-operative anemia [ 16 ]. In a large retrospective study with 2284 patients undergoing TKR, the authors reported that pre-operative anemia increased the rate of transfusion by 6.38 and 6.27 times in males and females, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%